2008
DOI: 10.1108/02651330810851872
|View full text |Cite
|
Sign up to set email alerts
|

Consumers' need for uniqueness: short‐form scale development and cross‐cultural validation

Abstract: PurposeThe purpose of this paper is to develop and validate cross‐culturally a short‐form, consumers' need for uniqueness (CNFU) scale. The length of the original scale (31 items) might have hindered its diffusion in research when questionnaire length and respondent fatigue are major considerations.Design/methodology/approachThe paper uses survey‐based data from Israel, Slovenia, and the Palestinian Authority and uses a combination of statistical techniques, such as EFA, CFA, and structural equation modeling.F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
180
0
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(191 citation statements)
references
References 58 publications
1
180
0
7
Order By: Relevance
“…This directly taps into brand and product ownership preferences with a high score indicating that participants had a stronger desire to avoid products bought by the majority of the population. 21 Finally, participants completed an Attitudes Towards the Mobile Phone as a Status Object (ATMPSO) scale. 22 …”
Section: Methodsmentioning
confidence: 99%
“…This directly taps into brand and product ownership preferences with a high score indicating that participants had a stronger desire to avoid products bought by the majority of the population. 21 Finally, participants completed an Attitudes Towards the Mobile Phone as a Status Object (ATMPSO) scale. 22 …”
Section: Methodsmentioning
confidence: 99%
“…Esse traço pode remeter ao individualismo, ainda que tenha sido encontrado tanto em sociedades coletivistas quanto individualistas (Hofstede, 2001;Ruvio, Shoham, & Brencic, 2008), porque a necessidade de exclusividade é oriunda do indivíduo e não do grupo social propriamente. Embora essas escolhas algumas vezes diferenciem um indivíduo dos outros, o resultado do consumo e seu simbolismo estão alinhados aos padrões pessoais do indivíduo (Nail, 1986).…”
Section: Consumo Simbólico E Necessidade De Exclusividadeunclassified
“…Studies have found that status seeking consumers are concerned with their peers and use brands to convey status [14]. Griskevicius discussed how people indulge in sustainable luxury just for the sake of status, a desire for status can spur self-sacrifice and present a powerful tool for motivating prosocial and proenvironmental action Need for uniqueness: The theory of consumers' need for uniqueness explains how an individual's need for uniqueness can influence brand responses and the need to be different from others Ryan [15]; [16] through the pursuit of material goods Knight & Kim [17].…”
Section: Derivatives Of Sustainable Behaviourmentioning
confidence: 99%